BEACH PROFILE CHANGES INDUCED BY STORMS - To, Dang Van (Vietnam Journal of Marine Science and Technology, 2008)
Along with the introduction of the SBEACH model. the storm-induced beach profile changes in the Gold Coast. Australia, were simulated using SBEACH with survey data collected in 1996. SBEA CH qualitatively modeled the profile changes: onshore erosion and offshore deposition. Quantitatively, SBEACH did not simulate accurately the shape of the measured profile change in spite of the correct estimation of the bar height. Numerical experiments are necessary to conduct in order to properly determine the empirical parameters for the accurate simulation of profile changes.